Preparation of'double-adsorption barrier 'composite material and application of'double-adsorption barrier' composite material in separation and purification of active ingredients of cistanche deserticola

A composite material with a 'double adsorption barrier' structure, using MXene-filled PVDF membranes and PEI/TA modifications, addresses the challenges of complex regeneration and low specificity in existing absorbent materials, achieving enhanced separation of Cordyceps sinensis components.

CN120305942APending Publication Date: 2025-07-15SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949514.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing adsorption method is difficult to regenerate and complex to operate in the separation of active ingredients of Cistanche, and the membrane separation method is simple to operate but limited to the application in the study of natural products. A composite material combining the two is needed to improve the separation efficiency.

Method used

Polyvinylidene fluoride (PVDF) is used as the matrix and MXene of the SWCNT-COOH intercalation is used as the filler, and combined with polyethyleneimine (PEI) and tannin (TA) modification, to construct a TCM composite material with a "dual adsorption barrier". The internal structure is built into a mesh structure, and the surface functional coating provides affinity sites.

Benefits of technology

The separation effect of the active ingredients of Cistanche salmoniae has been improved, the adsorption amount and selectivity have been significantly improved, and efficient separation performance has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005214525650000011
    Figure HDA0005214525650000011
  • Figure HDA0005214525650000012
    Figure HDA0005214525650000012
  • Figure HDA0005214525650000013
    Figure HDA0005214525650000013
Patent Text Reader

Abstract

The invention provides a functional coating-based composite material with a double-adsorption barrier structure, and relates to the field of material extraction. The preparation method comprises the following steps: mixing MXene (T3C2Tx) intercalated by a carboxylated carbon nanotube (SWCNT-COOH) with a membrane matrix polyvinylidene fluoride (PVDF) to obtain an MS-coated PVDF membrane with an inner-layer net structure; polyethyleneimine (PEI) / tannic acid (TA) is adopted to modify the surface of MS-coated PVDF to obtain the TCM film with double adsorption barriers. Compared with the prior art, the invention has the following advantages: the composite material provided by the invention constructs a'double-adsorption barrier 'structure, has the advantages of easy material recovery, low energy consumption, excellent separation performance, continuous separation and the like, and effectively overcomes the defects of difficult recovery, high energy consumption and the like. The composite material is designed by combining a membrane separation method and an adsorption method and can efficiently separate active components in cistanche, and a new application thought and method are expected to be provided for efficient separation of the active components in cistanche.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material separation, and particularly relates to the preparation of a TCM composite material with a "dual adsorption barrier" and its use for separating active ingredients from Cistanche tubulosa. Background Art

[0002] Cistanche tubulosa is a parasitic plant belonging to the genus Cistanche in the Orobanchaceae family. This traditional Chinese medicine has a long historical background and is famous for its tonic medicinal properties. Modern research has confirmed that Cistanche tubulosa has various biological activities such as anti-Alzheimer's, anti-aging, anti-fatigue, and immune regulation, and also has the medicinal effects of tonifying the kidney, replenishing essence, moistening dryness, and laxative. In addition, Cistanche has great development potential in many fields such as medicine, health care, and food, and has become an important raw material for many health products. Therefore, designing a material that can effectively separate and purify the active ingredients from Cistanche tubulosa is of great significance for improving its application value.

[0003] As an effective separation and purification technology, the adsorption method has made remarkable progress in the research field of natural products. In recent years, researchers have designed and developed a variety of new adsorption materials for the extraction and purification of active ingredients in natural products. These materials have the advantages of high selectivity, large adsorption capacity, and simple operation, providing strong support for the research of natural products. However, the difficult regeneration and complex operation of the adsorbents used in the adsorption method limit its wide application. The membrane separation technology has attracted wide attention in the research and application fields of natural products due to its advantages such as simple operation, low energy consumption, and easy recovery. Based on this, it is necessary to design a composite material that combines the advantages of the adsorption method and the membrane separation method.

[0004] The present invention provides a method for preparing a TCM composite material with a "dual adsorption barrier" structure and its use for separating active ingredients from Cistanche tubulosa. The composite material TCM has a layer network structure inside for adsorbing and intercepting the active ingredients in Cistanche tubulosa, and a functionalized coating on the surface for adsorbing the active ingredients in Cistanche tubulosa, which can provide affinity sites. The internal layer network structure and the surface functionalized coating work together to construct a "dual adsorption barrier" for separating the active ingredients in Cistanche tubulosa. Summary of the Invention

[0005] Aiming at the deficiencies in the prior art, the present invention provides a method for preparing a TCM composite material with a "dual adsorption barrier" structure and its application. The present invention uses polyvinylidene fluoride (PVDF) as the matrix and MXene intercalated with SWCNT-COOH as the filler to prepare MS@PVDF; and modifies the surface of MS@PVDF with polyethyleneimine (PEI) and tannic acid (TA) to obtain the TCM composite material. The composite material has a "dual adsorption barrier" structure and can work together to enhance the separation of the active ingredients from Cistanche tubulosa. The composite material has a good separation effect on the separation of the active ingredients from Cistanche tubulosa.

[0006] The present invention first provides a method for preparing a TCM composite material with a "double adsorption barrier" structure, which specifically includes the following steps:

[0007] (1) Preparation of MXene:

[0008] Disperse the precursor MAX (Ti3AlC2) into a mixed solution of LiF and concentrated hydrochloric acid (HCl), ultrasonically disperse and dissolve it, etch it by stirring and heating in an oil bath, centrifuge the etched product, wash it with ultrapure water until neutral, and dry it to obtain MXene (T3C2T x );

[0009] (2) Preparation of MXene intercalated with SWCNT-COOH:

[0010] The obtained layered MXene (T3C2T x ) is ultrasonically dispersed in ultrapure water to prepare a suspension, and the supernatant is taken by centrifugation; carboxylated carbon nanotubes (SWCNT-COOH) are added to ultrapure water to ultrasonically disperse the solution to obtain a SWCNT-COOH dispersion; the supernatant obtained by centrifugation and the SWCNT-COOH dispersion are stirred and mixed evenly, and the mixed product is centrifuged, and the obtained product is dried to obtain a layer reticular filler;

[0011] (3) Preparation of MS@PVDF:

[0012] Dissolve PVDF powder, polyvinylpyrrolidone (PVP) and MXene filler intercalated with SWCNT-COOH in N-methylpyrrolidone (NMP), stir in an oil bath, stand for degassing, scrape the film after degassing, and place the scraped film in ultrapure water for phase inversion reaction to obtain a MS@PVDF blend film, which is stored in ultrapure water for later use;

[0013] (4) Preparation of TCM composite material:

[0014] Disperse tannic acid (TA) into Tris-HCl buffer solution and ultrasonically mix evenly to prepare a TA buffer solution. Immerse the prepared MS@PVDF in the TA buffer solution, take it out and dry it, then evenly drop a mixed solution of ethanol and 3-aminopropyltriethoxysilane (APTES) with a volume ratio of 1:1 on the above MS@PVDF, add the TA buffer solution to the above mixed solution and react in an orbital shaker at room temperature. After washing away the surface impurities with ultrapure water, modified MS@PVDF-0 is obtained; Immerse MS@PVDF-0 in a mixed solution of tannic acid (TA) Tris-HCl buffer solution and polyethyleneimine (PEI) Tris-HCl buffer solution, react at room temperature, and finally wash with ultrapure water to obtain the final product TCM composite material.

[0015] Preferably, in step (1), MAX(Ti3AlC2) is 400 mesh, the ultrasonic dispersion power is 200 - 250 watts, the ultrasonic dispersion time is (3 - 5 min), the etching time is (35 - 40 h), the etching temperature is (35 - 40 °C), the centrifugation speed of the etching product is 6000 - 8000 revolutions per second, the centrifugation time is (8 - 10 min), it is washed with ultrapure water 6 - 8 times until neutral, the drying time is (10 - 12 h), and the drying temperature is (35 - 40 °C); the dosage ratio of the precursor MAX(Ti3AlC2), LiF for dispersion, and concentrated hydrochloric acid HCL is (0.8 - 1.0 g):(1.4 - 1.6 g):(20 - 22 ml);

[0016] Preferably, in step (2), the ultrasonic dispersion power of the supernatant is 200 - 250 watts, the ultrasonic dispersion time is (50 - 60 min), the centrifugation speed is 3500 - 4000 revolutions per second, the centrifugation time is (20 - 25 min), the ultrasonic dispersion power of the SWCNT-COOH dispersion is 200 - 250 watts, the ultrasonic dispersion time is (3 - 5 min), the stirring temperature of the mixed solution is (25 - 30 °C), the stirring time is (25 - 30 min), the centrifugation speed of the mixed product is 9000 - 10000 revolutions per second, the centrifugation time is (20 - 25 min), the drying temperature is (35 - 40 °C), and the drying time is (10 - 12 h); the dosage ratio of the layered MXene (T3C2T x ) and ultrapure water for dispersion is (0.70 - 1.0 g):(70 - 100 ml), and the supernatant after centrifugation is (5.0 - 8 g); the dosage ratio of carboxylated carbon nanotubes (SWCNT-COOH) and ultrapure water in the SWCNT-COOH dispersion is (0.0900 - 0.15 g):(30 - 50 ml); the dosage ratio of the supernatant in the mixed solution and the SWCNT-COOH dispersion is (2.0 - 3.0 g):(0.2 - 0.30 g).

[0017] Preferably, in step (3), the oil bath temperature is 45 - 55 °C, the stirring time is 24 - 25 h, the static degassing temperature is 45 - 55 °C, and the degassing time is (12 - 14 h); the dosage ratio of polyvinylidene fluoride powder, polyvinylpyrrolidone, the layer reticular filler, and N-methylpyrrolidone is (6.0 - 8.0 g):(0.1 - 0.2 g):(0.1 - 0.3 g):(22 - 24 g).

[0018] Preferably, in step (4), the dosage ratio of tannic acid (TA) and Tris-HCl buffer solution in the 10 mg / ml tannic acid (TA) buffer solution is (0.10 - 0.20 g) : (10 - 20 ml); the soaking time is (30 - 40 min); the dosage ratio of ethanol and 3-aminopropyltriethoxysilane (APTES) in the ethanol and 3-aminopropyltriethoxysilane (APTES) mixed solution is (5 - 10 ml) : (5 - 10 ml); the time for uniform dropwise coating is (5 - 10 min); the dosage ratio of tannic acid and Tris-HCl buffer solution in the 2 mg / ml tannic acid (TA) buffer solution is (0.02 g - 0.04 g); 2 mg / ml TA; the dosage ratio of the ethanol and 3-aminopropyltriethoxysilane (APTES) mixed solution and the 2 mg / ml tannic acid (TA) buffer solution is (5 - 10 ml) : (10 - 20 ml); the oscillation reaction time is (12 - 14 h); the ultra-pure water washing time is (3 - 5 min); the dosage ratio of polyethyleneimine (PEI) and Tris-HCl buffer solution in the 3 ml / mg polyethyleneimine (PEI) buffer solution is (0.03 - 0.045 g) : (10 - 15 ml); the dosage ratio of the 3 ml / mg polyethyleneimine (PEI) buffer solution and the 2 mg / ml tannic acid (TA) buffer solution in the mixed solution of the 3 ml / mg polyethyleneimine (PEI) buffer solution and the 2 mg / ml tannic acid (TA) buffer solution is (10 - 15 ml) : (10 - 15 ml); the time for the MS@PVDF-0 membrane to be immersed in the above mixed solution is (2 - 8 h).

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] The TCM composite material of the present invention combines the advantages of a functionalized membrane material and an adsorbent, and has a surface with affinity sites and a layer-network internal structure. The present invention combines the SWCNT-COOH intercalated MXene filler with the polyvinylidene fluoride membrane matrix to construct a layer-network structure in the membrane for the adsorption and interception of the active ingredients of Cistanche deserticola; the surface is modified with PEI / and TA to construct a functionalized coating rich in amino and hydroxyl functions, which can have an affinity with the active ingredients in Cistanche deserticola and improve the selectivity for the active ingredients. The constructed "dual adsorption barrier" structure can act synergistically to effectively improve the separation performance of the active ingredients in Cistanche deserticola.

[0021] The TCM composite material described in the present invention combines the advantages of membrane materials and adsorption materials, and through their synergistic effect, the layered structure of MXene intercalated with SWCNT-COOH regulates the pore size and internal structure of the polyvinylidene fluoride membrane matrix, and constructs a layered structure inside for the adsorption and interception of the active ingredients of Cistanche deserticola; the surface modified with PEI / and TA has abundant amino and hydroxyl groups, which can have an affinity with the active ingredients in Cistanche deserticola and enhance selectivity. The test results show that the adsorption capacity and adsorption selectivity of the TCM composite material for the active ingredients in Cistanche deserticola are 138.06 mg / g and 3.06 respectively, and the permeation selectivity is 4.68, providing a new strategy for the effective separation of the active ingredients of Cistanche deserticola. Description of the Drawings

[0022] Figure 1 Scanning electron micrograph of the surface of the MS@PVDF membrane prepared in Example 1.

[0023] Figure 2 Scanning electron micrograph of the surface of the TCM membrane prepared in Example 1.

[0024] Figure 3 Scanning electron micrograph of the surface of the PVDF membrane prepared in Comparative Example 1. Detailed Description of the Invention

[0025] The present invention will be further described below in conjunction with the drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] Example 1: Preparation of the TCM Composite Material

[0027] (1) Preparation of MXene:

[0028] 1 g of the precursor MAX (Ti3AlC2) is added to a 200 ml polytetrafluoroethylene container, then 1.0 g of LiF and 20 ml of concentrated hydrochloric acid HCL are added and mixed evenly, and etched by stirring at 40 °C for 48 h. After the etching is completed, it is washed multiple times until the supernatant is neutral, and dried for 12 h to obtain the product MXene

[0029] (2) MXene Intercalated with SWCNT-COOH:

[0030] Take 1 g of MXene and disperse it in 20 ml of ultrapure water. After ultrasonic treatment for 30 min, 50 mg of SWCNT-COOH is added, and stirred at room temperature for 1 h to mix evenly. After centrifugation, it is freeze-dried for 24 h to obtain MXene intercalated with SWCNT-COOH.

[0031] (3) Preparation of MS@PVDF:

[0032] Add 200 mg of SWCNT-COOH intercalated MXene, 8 g of polyvinylidene fluoride powder, 200 mg of polyvinylpyrrolidone, and an aqueous solution of 23 g of N-methylpyrrolidone to a 100 ml round-bottom flask, stir mechanically for 24 h, with the oil bath temperature at 50 °C. After stirring, let it stand for degassing for 12 h at a temperature of 45 - 55 °C. After the reaction, use a casting knife to take out the casting solution and start scraping the film. Place the scraped film in deionized water for phase inversion reaction to obtain MS@PVDF for standby.

[0033] (4) Preparation of TCM composite

[0034] Soak the dried MS@PVDF in a 20 ml buffer solution of 10 mg / ml tannic acid (TA) for 30 min. After taking it out and drying, evenly drip a mixed solution with a volume ratio of ethanol to 3-aminopropyltriethoxysilane (APTES) of 1:1 on the above MS@PVDF membrane. Mix the above solution with 10 ml of a buffer solution containing 2 mg / ml tannic acid (TA) and react in an orbital shaker at room temperature for 12 h. Wash away the surface impurities with ultrapure water to obtain modified MS@PVDF-0. Soak the dried MS@PVDF-0 in a mixed solution of 10 ml of a 3 mg / ml polyethyleneimine (PEI) buffer solution and 10 ml of a 2 mg / ml tannic acid (TA) buffer solution for 6 h. Wash away the impurities on the membrane surface with ultrapure water to obtain the TCM composite.

[0035] The surface scanning electron microscope images of the MS@PDVF and TCM membranes are as Figure 1 and Figure 2 shown. It can be seen from the SEM in Figure 1 that due to the introduction of the SWCNT-COOH intercalated MXene filler, the MS@PVDF membrane has a uniform pore structure. It can be seen from the SEM in Figure 2 that due to the construction of the functionalized coating of polyethyleneimine (PEI) and tannic acid (TA), the surface of the TCM membrane is smoother and the pores are reduced.

[0036] In this example, the adsorption and separation test of the active ingredient crude extract in Cistanche deserticola by the TCM composite was also investigated at 30 °C and 150 r / min. The test results show that the adsorption capacity and selectivity of the TCM composite for the active ingredient in Cistanche deserticola are 133.62 mg / g and 2.68 respectively.

[0037] Example 2:

[0038] In this example, the TCM composite was prepared by the method described in Example 1, with only the following difference: in step (4), the soaking time of MS@PVDF-0 in the mixed solution was different, that is, the soaking time of 6 h was changed to 2 h.

[0039] In this example, the adsorption and separation test of the crude extract of active ingredients in Cistanche deserticola by the TCM composite material was also investigated under the conditions of 30 °C and 150 r / min. The test results show that the adsorption capacity and selectivity of the TCM composite material for the active ingredients in Cistanche deserticola are 76.44 mg / g and 2.08 respectively.

[0040] Example 3:

[0041] In this example, the TCM composite material was prepared by the method described in Example 1, with only the following difference: the soaking time of MS@PVDF-0 in the mixed solution in step (4) was different, that is, the soaking time of 6 h was changed to 4 h.

[0042] In this example, the adsorption and separation test of the crude extract of active ingredients in Cistanche deserticola by the TCM composite material was also investigated under the conditions of 30 °C and 150 r / min. The test results show that the adsorption capacity and selectivity of the TCM composite material for the active ingredients in Cistanche deserticola are 94.75 mg / g and 2.23 respectively.

[0043] Example 4:

[0044] In this example, the TCM composite material was prepared by the method described in Example 1, with only the following difference: the soaking time of MS@PVDF-0 in the mixed solution in step (4) was different, that is, the soaking time of 6 h was changed to 8 h.

[0045] In this example, the adsorption and separation test of the crude extract of active ingredients in Cistanche deserticola by the TCM composite material was also investigated under the conditions of 30 °C and 150 r / min. The test results show that the adsorption capacity and selectivity of the TCM composite material for the active ingredients in Cistanche deserticola are 135.77 mg / g and 2.68 respectively.

[0046] Example 5:

[0047] In this example, the TCM composite material was prepared by the method described in Example 1, with only the following difference: the soaking time of MS@PVDF-0 in the mixed solution in step (4) was different, that is, the soaking time of 6 h was changed to 10 h.

[0048] In this example, the adsorption and separation test of the crude extract of active ingredients in Cistanche deserticola by the TCM composite material was also investigated under the conditions of 30 °C and 150 r / min. The test results show that the adsorption capacity and selectivity of the TCM composite material for the active ingredients in Cistanche deserticola are 129.55 mg / g and 2.76 respectively.

[0049] Comparative Example 1:

[0050] Preparation of PVDF membrane: 8g of PVDF powder and 0.1g of polyvinyl pyrrolidone were dissolved in 23g of N-methylpyrrolidone, mechanically stirred at 50°C in an oil bath for 24h, and then allowed to stand at 50°C for 12h for degassing. The casting solution was taken out with a casting knife and the film was scraped. The scraped film was placed in deionized water for phase inversion reaction, and finally the resulting PVDF membrane was obtained.

[0051] This example also examines the adsorption and separation test of the crude extract of active ingredients in Cistanche deserticola by PVDF membrane at 30°C and 150r / min. The test results show that the adsorption amount and selectivity of the PVDF membrane for the active ingredients in Cistanche deserticola are 27.03 mg / g and 1.12 respectively.

[0052] The scanning electron microscope of the surface of the PVDF membrane of the material is as follows Figure 3 ,From SEM, it can be seen that the PVDF membrane surface ,pores without the introduction of MXene filler of SWCNT-COOH intercalation are uneven and have a blocky ,structure.

[0053] In summary, the TCM composite material described in the present invention combines the advantages of membrane materials and adsorption materials, and the layer network structure of the introduced SWCNT-COOH intercalated MXene adjusts the pore size and internal structure of the polyvinylidene fluoride membrane matrix, and constructs a layer network structure for adsorption and interception of the active ingredients of Cistanche deserticola; the surface modified by PEI / and TA has rich amino and hydroxyl groups, which can produce affinity with the active ingredients in Cistanche deserticola to enhance selectivity.

[0054] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A preparation method of a "dual adsorption barrier" composite material TCM, characterized in that, The preparation method of the TCM composite material includes the following steps: (1) Preparation of MXene: Disperse the precursor MAX (Ti3AlC2) into a mixed solution of LiF and concentrated hydrochloric acid (HCl), ultrasonically disperse and dissolve it, etch it by stirring and heating in an oil bath, centrifuge the etched product, wash it neutral with ultrapure water, and dry it to obtain MXene (T3C2T x ); (2) Preparation of SWCNT-COOH intercalated MXene: The obtained layered MXene (T3C2T x ) was ultrasonically dispersed in ultrapure water to prepare a suspension, and the supernatant was taken by centrifugation; carboxylated carbon nanotubes (SWCNT-COOH) were added to ultrapure water to obtain a SWCNT-COOH dispersion by ultrasonic dispersion; the supernatant obtained by centrifugation and the SWCNT-COOH dispersion were stirred and mixed evenly, and the mixed product was centrifuged. The obtained product was dried to obtain a layered network filler; (3) Preparation of MS@PVDF: Dissolve PVDF powder, polyvinylpyrrolidone (PVP), and SWCNT-COOH intercalated MXene filler in N-methylpyrrolidone (NMP), stir in an oil bath, stand for degassing, scrape the film after degassing, and place the scraped film in ultrapure water for phase inversion reaction to obtain the MS@PVDF blend film, which is stored in ultrapure water for later use; (4) Preparation of the TCM composite material: Disperse tannic acid (TA) in Tris-HCl buffer solution and mix evenly by ultrasonic to prepare the TA buffer solution. Immerse the prepared MS@PVDF in the TA buffer solution, take it out and dry it, then evenly drop the mixed solution of ethanol and 3-aminopropyltriethoxysilane (APTES) with a volume ratio of 1:1 on the above MS@PVDF. Add the TA buffer solution to the above mixed solution and react in an orbital shaker at room temperature. Wash away the surface impurities with ultrapure water to obtain modified MS@PVDF-0. Immerse MS@PVDF-0 in the mixed solution of tannic acid (TA) Tris-HCl buffer solution and polyethyleneimine (PEI) Tris-HCl buffer solution, react at room temperature, and finally wash with ultrapure water to obtain the final product TCM composite material.

2. The preparation method according to claim 1, wherein ; (1) In the above step (1), MAX (Ti3AlC2) is 400 mesh, the ultrasonic dispersion power is 200 - 250 watts, the ultrasonic dispersion time is 3 - 5 minutes, the etching time is 35 - 40 h, the etching temperature is 35 - 40 °C, the centrifugation speed of the etching product is 6000 - 8000 revolutions per second, the centrifugation time is 8 - 10 minutes, wash with ultrapure water 6 - 8 times until neutral, the drying time is 10 - 12 h, and the drying temperature is 35 - 40 °C; the dosage ratio of the precursor MAX (Ti3AlC2), dispersing LiF, and concentrated hydrochloric acid HCL is (0.8 - 1.0 g):(1.4 - 1.6 g):(20 - 22 ml). (2)In step (2), the ultrasonic dispersion power for obtaining the supernatant is 200 - 250 watts, the ultrasonic dispersion time is 50 - 60 minutes, the centrifugation speed is 3500 - 4000 revolutions per second, the centrifugation time is 20 - 25 min. The ultrasonic dispersion power of the SWCNT-COOH dispersion is 200 - 250 watts, the ultrasonic dispersion time is 3 - 5 min. The stirring temperature of the mixed solution is 25 - 30 °C, the stirring time is 25 - 30 min. The centrifugation speed of the mixed product is 9000 - 10000 revolutions per second, the centrifugation time is 20 - 25 min, the drying temperature is 35 - 40 °C, and the drying time is 10 - 12 h; the dosage ratio of the layered MXene (T3C2T x ) and the ultrapure water for dispersion is (0.70 - 1.0 g) : (70 - 100 ml), and the supernatant after centrifugation is (5.0 - 8 g); the dosage ratio of the carboxylated carbon nanotubes (SWCNT-COOH) and the ultrapure water in the SWCNT-COOH dispersion is (0.0900 - 0.15 g) : (30 - 50 ml); the dosage ratio of the supernatant in the mixed solution and the SWCNT-COOH dispersion is (2.0 - 3.0 g) : (0.2 - 0.30 g); (3) In step (3), the oil bath temperature is 45 - 55 °C, the stirring time is 24 - 25 h, the standing degassing temperature is 45 - 55 °C, and the degassing time is 12 - 14 h; the dosage ratio of polyvinylidene fluoride powder, polyvinylpyrrolidone, layered network filler, and N-methylpyrrolidone is (3.0 - 4.0 g):(0.1 - 0.2 g):(0.1 - 0.3 g):(22 - 24 g); (4) In step (4), the dosage ratio of tannic acid (TA) to Tris-HCl buffer solution in the 10 mg / ml tannic acid (TA) buffer solution is (0.10 - 0.20 g) : (10 - 20 ml); the soaking time is (30 - 40 min); the dosage ratio of ethanol to 3-aminopropyltriethoxysilane (APTES) in the ethanol and 3-aminopropyltriethoxysilane (APTES) mixed solution is (5 - 10 ml) : (5 - 10 ml); the time for uniform dropwise coating is (5 - 10 min); the dosage ratio of tannic acid to Tris-HCl buffer solution in the 2 mg / ml tannic acid (TA) buffer solution is (0.02 g - 0.04 g); 2 mg / ml TA; the dosage ratio of the ethanol and 3-aminopropyltriethoxysilane (APTES) mixed solution to the 2 mg / ml tannic acid (TA) buffer solution is (5 - 10 ml) : (10 - 20 ml); the oscillation reaction time is (12 - 14 h); the ultra-pure water washing time is (3 - 5 min); the dosage ratio of polyethyleneimine (PEI) to Tris-HCl buffer solution in the 3 ml / mg polyethyleneimine (PEI) buffer solution is (0.03 - 0.045 g) : (10 - 15 ml); the dosage ratio of the 3 ml / mg polyethyleneimine (PEI) buffer solution to the 2 mg / ml tannic acid (TA) buffer solution in the mixed solution of the 3 ml / mg polyethyleneimine (PEI) buffer solution and the 2 mg / ml tannic acid (TA) buffer solution is (10 - 15 ml) : (10 - 15 ml); the time for the MS@PVDF-0 membrane to be immersed in the above mixed solution is (2 - 8 h).

3. The preparation of a "dual adsorption barrier" composite material TCM according to claim 1 and its application in the separation and purification of active ingredients in Cistanche deserticola Ma.

4. A mixed membrane, wherein the mixed membrane uses SWCNT-COOH intercalated MXene as a filler and polyvinylidene fluoride as a base material. The filler and the base material form a mixed membrane through physical blending phase inversion, and a functionalized coating is formed on the surface of the mixed membrane by a chemical grafting method; the active ingredient in Cistanche deserticola Ma is acteoside.

5. The application of the mixed membrane according to claim 4 in the separation and purification of active ingredients in Cistanche deserticola Ma.